2002
DOI: 10.1093/ptj/82.5.459
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Musculoskeletal Disorders and the Culture of Physical Therapy

Abstract: Background and Purpose. Knowledge, skills, relationships, and attitudes of caring and working hard are all thought to be valued by physical therapists. This article explores how physical therapists see themselves, in light of some of these values, when they experience work-related musculoskeletal disorders (WMSDs). The article also explores the ways in which these values may compete with each other, and it suggests how this may contribute to the onset of WMSDs and to therapists' behavior following a WMSD. Subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 30 publications
2
47
1
4
Order By: Relevance
“…Ciarlini et al demonstraram que quanto maior o tempo de profissão do fisioterapeuta, maior o risco de desenvolver doenças profissionais em virtude da exposição contínua, ao longo dos anos, à sobrecarga osteomioarticular [23]. No entanto, alguns estudiosos têm evidenciado, em suas pesquisas, maior proporção de fisioterapeutas com menos tempo de experiência profissional relatando dor/desconforto musculoesquelético, atribuindo a esses a inexperiência na aquisição de estratégias para evitar os sintomas [3,4,24]. Segundo Peres, a carga horária/dia de trabalho e a frequência de atendimentos por dia refletem sobrecarga física, situação que produz diversas alterações musculoesqueléticas, principalmente desvios posturais, expondo o profissional a riscos de sua saúde [5].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Ciarlini et al demonstraram que quanto maior o tempo de profissão do fisioterapeuta, maior o risco de desenvolver doenças profissionais em virtude da exposição contínua, ao longo dos anos, à sobrecarga osteomioarticular [23]. No entanto, alguns estudiosos têm evidenciado, em suas pesquisas, maior proporção de fisioterapeutas com menos tempo de experiência profissional relatando dor/desconforto musculoesquelético, atribuindo a esses a inexperiência na aquisição de estratégias para evitar os sintomas [3,4,24]. Segundo Peres, a carga horária/dia de trabalho e a frequência de atendimentos por dia refletem sobrecarga física, situação que produz diversas alterações musculoesqueléticas, principalmente desvios posturais, expondo o profissional a riscos de sua saúde [5].…”
Section: Discussionunclassified
“…As posturas estáticas ou dinâmicas em posição de pé, com movimentos repetitivos de membros superiores, associadas à flexão de tronco e cervical e movimentos de rotação de tronco foram as posturas de trabalho mais citadas pelos voluntários durante sua prática clínica, concordando com os resultados encontrados por Peres [5]. Diversos estudos observaram que a maioria desses eventos posturais está associada ao risco de desenvolvimento de desconforto musculoesquelético em fisioterapeutas, limitando a sua capacidade de trabalho e/ou levando-os ao absenteísmo e afastamento [3,4,16,21].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…This, however, was inversely related to age where analysis showed that younger therapists reported more neck, upper back, low back, and thumb symptoms than older therapists did. 3 Participants in the study of Cromie et al (2002) did not anticipate WMSD and typically believed that their knowledge and skills would have prevented WMSD from occurring. They saw themselves as knowledgeable and caring and indicated that these characteristics were highly valued in their profession.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be influenced by internal factors for example, a belief that work-related discomfort is inevitable 7,10 or a desire to place a patient's needs above one's own. 7,[11][12][13][14] An online questionnaire sent to Australian optometrists in 2008 established that work-related discomfort is an issue within the optometric profession. Although this questionnaire enabled the identification of independent risk factors for work-related discomfort 8 and provided a better understanding of the variety of ways optometrists manage work-related discomfort, 9 it also raised many questions, such as, why do optometrists continue to work while injured?…”
mentioning
confidence: 99%